Programa de mantenimiento centrado en confiabilidad para bombas centrifugas horizontales warman 450 mcr en Minera Cerro Corona - Santillan Armas, Cristian Paul (2017)
The present study proposes the application of a maintenance program focused on reliability for horizontal centrifugal pumps Warman 450 MCR developed in the mining project Cerro Corona, with the aim of increasing its availability. The application of reliability is based on a criticality analysis of the equipment and then based on the seven questions of the RCM define the main function, functional failure, failure modes, effects and consequences, analyze if there is a proactive maintenance and if not analyze a Change in equipment design. Then with the data of the SAP software of the company we elaborated a graph of dispersion of the faults, where we identify the chronic and acute faults that are generating the unavailability of the equipment. Then, we apply the Weibull statistical model to the two failure modes identified, as well as using the cost curve as a decision tool to obtain the equipment intervention optimization time. It is concluded that the failure modes that generate unavailability due to reliability and maintainability are the GAP Regulation and the Dish Change and Suction Liners. It also shows the reliability and cost curves that will help to make decisions about the intervention time, the reliability and the associated cost.